I Flunked, But ... - Hughes, Ed (The Ozu Collection, 2011)
A college student's (Tatsuo Saito) underhanded scheme to cheat on his final examinations backfires when the boarding house matron sends the shirt on which he has scribbled his notes out for laundry. Now faced with remaining as a student for another year and bearing the dubious distinction of being the only student in the household who did not graduate, he gradually adjusts to the reality of his deferred professional life, eventually turning his disappointment to optimism with the support and encouragement of his friends and a young waitress (Kinuyo Tanaka) who is devoted to him. Similar to the lighthearted comedy of "Days of Youth", "I Flunked But ..." is a hilarious and effervescent comedy on a young man's unforeseen (and unintentionally) delayed passage to maturity and responsibility. [www.filmref.com]